2021
DOI: 10.1007/s10694-021-01179-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parallel Curtain Walls on Upward Flame Spread Characteristics and Mass Loss Rate Over PMMA

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…These studies largely focused on different fuel attributes (e.g. area density, 1,2 sample width), [2][3][4] ambient conditions (pressure, 3,5 oxygen concentration, 3,[5][6][7] flow speed), 5,6,8 flow confinement, 9,10 and sample inclination angle. 11,12 It was observed that upward flame spread under normal gravity is one of the most hazardous flame spread scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…These studies largely focused on different fuel attributes (e.g. area density, 1,2 sample width), [2][3][4] ambient conditions (pressure, 3,5 oxygen concentration, 3,[5][6][7] flow speed), 5,6,8 flow confinement, 9,10 and sample inclination angle. 11,12 It was observed that upward flame spread under normal gravity is one of the most hazardous flame spread scenarios.…”
Section: Introductionmentioning
confidence: 99%